Cultural Factors and deviant behaviour among Secondary School Students in Southwest Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2025)
There is no doubt that deviant behaviour among secondary school students could be determined by many factors among which is cultural factors such as family influence and religion influence. This study investigated the influence of cultural factors on deviant behaviour among secondary school students in Southwest Nigeria. A descriptive survey research design was employed. The study population comprised 31,144 male and female students enrolled in both public and private secondary schools across the Southwest region of Nigeria. Using a multistage sampling technique, a total of 1,777 students were selected from these schools to participate in the study. An instrument designed by the researcher titled ‘Questionnaire on Cultural factors and deviant behaviour among secondary school students (CFDBSSS) was used to elicit data for this study. The instrument was validated by experts and subjected to reliability test through Cronbach's Alpha reliability test which yielded a reliability coefficient of 0.82. Two hypotheses were tested at 0.05 level of significance using Pearson Production Moment Correlation. Findings of the study revealed that family and religion influence had significant relationship with deviant behaviour among secondary schools’ students in Southwest Nigeria. It was recommended among others that parents should make it a priority that their children get to schools on time to avoid lateness this will enhance their positive behaviour, religious leaders in their sermons should dwell much on morality as well as moral upbringing of children, Pragmatic and spiritual consequences of immoralities should equally be emphasized to avoid negative influence. Keywords: family influence, religion influence, deviant